2021
DOI: 10.1093/jat/bkab048
|View full text |Cite
|
Sign up to set email alerts
|

In a Case of Death Involving Steroids, Hair Testing is More Informative than Blood or Urine Testing

Abstract: A 59-year old male was found dead at home, with 2 empty vials of an oily preparation attributed to a manufacturer from East Europe. There was no label on the vial. The subject was a former weightlifter, also known as an anabolic steroids abuser. The local prosecutor ordered a body examination, which was unremarkable and allowed collecting femoral blood, urine and scalp hair (6 cm, brown). He was treated for cardiac insufficiency with quinidine. Biological specimens were submitted to standard toxicological anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 28 publications
2
9
1
Order By: Relevance
“…In interpreting the concentrations of anabolic steroids in the post-mortem phase, it is necessary to consider that anabolic steroids have a poor incorporation in hair and that a single dose of 50 mg of some of them (nandrolone undecanoate, nandrolone decanoate, testosterone enanthate, testosterone undecanoate, and testosterone propionate) is undetectable in the hair. 33 Thus, identification of AAS in the hair sample confirms the frequent/chronic use of those substances and contributes to establishing hair analysis as the best approach to document the current/past abuse of anabolic agents. Anatomopathological findings are consistent with this assumption: cardiac hypertrophy and widespread presence of fibroatheromatic plaques in coronary arteries.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In interpreting the concentrations of anabolic steroids in the post-mortem phase, it is necessary to consider that anabolic steroids have a poor incorporation in hair and that a single dose of 50 mg of some of them (nandrolone undecanoate, nandrolone decanoate, testosterone enanthate, testosterone undecanoate, and testosterone propionate) is undetectable in the hair. 33 Thus, identification of AAS in the hair sample confirms the frequent/chronic use of those substances and contributes to establishing hair analysis as the best approach to document the current/past abuse of anabolic agents. Anatomopathological findings are consistent with this assumption: cardiac hypertrophy and widespread presence of fibroatheromatic plaques in coronary arteries.…”
Section: Discussionmentioning
confidence: 86%
“…Furthermore, concentrations of other two synthetic steroids, boldenone and nandrolone, compared with the existing literature 28 suggest that the decedent was a regular anabolic steroid abuser. In interpreting the concentrations of anabolic steroids in the post‐mortem phase, it is necessary to consider that anabolic steroids have a poor incorporation in hair and that a single dose of 50 mg of some of them (nandrolone undecanoate, nandrolone decanoate, testosterone enanthate, testosterone undecanoate, and testosterone propionate) is undetectable in the hair 33 …”
Section: Discussionmentioning
confidence: 99%
“…Favretto et al reported a testosterone hair concentration of 18 pg/mg for a testosterone undecanoate user, 13 143 pg/mg. 11,12,36 These values are below our method LOD. Few papers reported hair concentration levels for sildenafil.…”
Section: Discussionmentioning
confidence: 66%
“…The concentrations measured in head hair were comparable or higher to the ones found by other authors for chronic users. In particular, stanozolol was detected in the hair from 2 up to 881 pg/mg, [27][28][29] methandienone levels in hair ranged from 3 to 206 pg/mg, 11,[29][30][31] and testosterone enanthate from 0.6 up to 18.8 ng/mg. 32 Also, testosterone was in a concentration higher than those reported for endogenous contribution, which ranged from 0.3 to 11.81 pg/mg.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation